Practice and Determinants of Breast Self-Examination Among Women in Chereponi District, Northern Region of Ghana - Oteng, Joseph (Darul Yasin Al Sys, 2025)
Breast cancer is a public health problem in Ghana and early detection is a key determinant to the survival rate of the disease. It is a preventive measure usually encouraged among women to examine their breasts by feeling them several times a month for any lumpiness or hardness. The study was conducted to find out the practice and determinants of BSE among women in the Chereponi district in the northern region of Ghana. Method: A community-based cross-sectional research design with a mixed methods approach was utilized among 384 women aged 18 - 49 years in the Chereponi district. Participants were recruited using a multistage sampling technique with a structured questionnaire and Key Informant Interviews for data collection. The descriptive and inferential data were analysed using the SPSS and NVIVO. Results: The finding reveals that the participants were abreast with Breast self-examination (BSE) techniques. The bivariate correlation study of the level of knowledge and BSE also indicated strong positive relationship between the two variables. In other words, a two-tailed Pearson correlation coefficient of 0.777 shows positive significant relationship between the two variables at 0.01 level. Conclusion: The practice of BSE was found to have a direct relationship with the knowledge. Though the practice was commendable among those who had the knowledge, there were still challenges of cultural and social norms that mitigated against the practice of breast self-examination. It is important to empower women, promote supportive relationships and maximise women’s social networks to promote BSE uptake at the community level.